Perception Of Teacher's Technology Adoption On Students’ Achievement In Social Studies In Osun State, Nigeria - Ibikunle, Yejide Adepeju; Ogunsanmi, Olawale Ayoola; LIjofi, Victor Abiodun (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
Effective integration of technology in education hinges upon teachers' perception, readiness, and pedagogical skills despite its diverse tools and platforms for interactive learning and accessing resources. The study assessed the current level of technology adoption and utilization among social studies teachers in Osun State, investigated the correlation between their perceived effectiveness and students' academic achievement, and identified influencing factors. The descriptive survey research design was adopted in the study. A sample of 144 teachers was used through the multi-stage sampling procedure. A self-developed instrument titled Perception of Teacher's Technology Adoption Questionnaire (PTTAQ) and student exam records in Social Studies were used as research instruments for data collection. The Cronbach Alpha estimate of the PTTAQ was 0.86. Data collected were analysed using appropriate descriptive and inferential statistics. The result showed that the level of adoption is moderate (mean = 2.48, S.D=1.48), and utilization is moderate (mean = 2.46, S.D=1.37). Also, results show there is no correlation between teachers’ perceived effectiveness of technology adoption and students' academic achievement in social studies (r = -.081, p > .05). The perceived factors influencing teachers' attitudes toward technology adoption are technology self-efficacy, attitudes toward change, school culture and support, development and training opportunities on technology, perceptions of effectiveness, time and resource constraints. The study concluded that there were mixed perceptions of technology adoption among social studies teachers due to moderate levels of adoption and utilization. Ongoing programs, support, and resources are recommended to bolster teachers' technology self-efficacy for effective pedagogical practices.